Substantiation of parameters for the technological process of restoring machine parts by the method of plastic deformation - Dudnikov, Anatolii; Dudnik, Vladimir; Ivankova, Olena; Burlaka, Oleksii (Eastern-European Journal of Enterprise Technologies, 2019)
We have studied technological processes related to the restoration of worn-out parts of agricultural machinery (plowshares, cultivator sweeps) that operate under conditions of intensive abrasive wear. We have determined the influence of operating parameters of the technological process on the quality of the restored surface of the cutting elements of machines’ working bodies under conditions of regular and vibration deformation. It was noted that the restoration technologies based on vibratory oscillations make it possible to create new machining methods characterized by higher intensity: the physical-mechanical properties of the recovered parts’ material, their shape and dimensions, as well as machining regimes. We have performed a strain gauge study of changes in the parameters of cutting elements in the working bodies of tillage machines, which made it possible to determine the magnitude of deformation when parts are machined. We have constructed a mathematical model of the dynamics of abrasive wear of the above-specified working bodies, which allowed us to define the patterns in the wear intensity distribution of a working body’s cutting element. Based on the derived curves of density distribution of wear magnitudes for cutting elements in the specified parts, we have defined a wear law that revealed patterns of change in the strained-stressed state of the working surface in a cutting element. We have estimated the influence of basic factors on the processes occurring in the material of parts during operation. The main factors for vibration machining of the parts’ working surface have been established: the amplitude, frequency of oscillations of a machining tool, the time of hardening. The criteria for the threshold condition of parts under conditions of abrasive wear have been defined: the thickness of edge of the cutting element of parts and a change in size. We have established the positive role of compressive stresses when machining the parts’ material in their wear-resistance improvement. A dependence of the magnitude of parts’ wear on the following key factors has been established: their material, restoration technique, operation duration. It has been proven that the use of vibratory oscillations of the machining working body reduces the intensity of wear of parts in tillage machinery, which is important and relevant to improving the reliability of agricultural machines